Genetics of the acute coronary syndrome - Franchini, Massimo (Annals of Translational Medicine; Vol 4, No 10 (May 25, 2016): Annals of Translational Medicine (Focus on “State of the Art in Diagnostics of the Acute Coronary Syndrome”), 2016)
Acute coronary artery syndrome in the leading cause of morbidity and mortality in Western countries, and its epidemiological burden is also constantly increasing worldwide, including Asia. Due to social and economic consequences, a number of experimental and epidemiological studies have analyzed its etiology so far, in order to develop effective preventive and treatment measures. Thanks to these studies, it is now clear that coronary artery disease (CAD) is a complex multifactorial disorder, resulting from close interaction between acquired and inherited risk factors. In particular, considerable advances were made in the last decade about our understanding of the genetic causes of CAD, mainly propelled by the progresses in whole genome scanning and the development of genome wide association studies. This narrative review is hence dedicated to explore the role of genetic factors in the risk of developing acute CAD.